Dual morphology titanium dioxide for dye sensitized solar cells. Issue 6 (15th April 2019) - Selvapriya, R.; Mayandi, J.; Ragavendran, V.; Sasirekha, V.; Vinodhini, J.; Pearce, J.M.
Abstract: Anatase TiO2 displaying dual morphologies were synthesized with a simple chemical route via a single step. A strong correlation between the dye sensitized solar cell (DSSC) device performance and the obtained dual morphologies are highlighted using relevant evidences from UV–vis and diffuse reflectance spectroscopy (DRS), Raman analysis, field emission scanning electron microscope, high resolution transmission electron microscope, current-voltage characteristics and impedance analysis. Structural investigation revealed that the interested medium in this work employed for the synthesis of TiO2 produced different types of dual morphologies such as nanospheres with nanoparticles (NSNP), microsphere decorated with nanoparticles (μSNP) and nanoparticles with stone like features (NPS). UV–vis and DRS results indicated the ability of the materials to assist with diffused reflectance and optical absorption of the screen printed photoanodes. In addition, an investigation of Raman vibrational characteristics was carried out in detail using synchronous and asynchronous 2D correlation analysis. The high intense Eg anatase mode of Raman spectrum was simulated using a phonon confinement model and its normalized spectra are compared with an experimental data. The resultant performances in the DSSCs were not indicative by the material properties; so, the charge transfer resistance (Rct ) and recombination properties of the photoanode were investigated. These results showed that the Nyquist plot of NSNP possesses the smallest diameter, which reveals that the device based on NSNP offers the lowest Rct value that accounts for the higher conversion efficiencies when compared with the DSSC device based on photoanodes μSNP and NSP. It can be concluded that the improved power conversion efficiency shown by photoanode fabricated using NSNP has the dual role of optimum surface area for dye loading and light scattering centres. These properties, when optimized along with the offered pathway for electrolyte diffusion to the dye degeneration with less Rct, could lead to better photoelectric conversion efficiency.